Penerapan Pemasaran Digital pada Warung Gondrong - Santi Rimadias; Glen Andrian Prawinata; Angel Avrilia; Carren Vivien; Frederick Amadeo Jonathan; Gilbert Giofflen; Julia Sara Felita; Vellyta (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
Digital marketing is now an important factor in spurring the growth of Micro, Small and Medium Enterprises (MSMEs). The owner lacks knowledge in selling and marketing his stall online. In order to optimize this potential, the focus of this team's community service is to implement a digital marketing strategy at Warung Gondrong. This was realized through Warung Gondrong's presence on social media platforms such as Instagram and TikTok, as well as the utilization of creative banners. The main goal is to increase sales by designing attractive content and adjusting marketing strategies to the characteristics of these MSMEs. Through the application of structured methods, the implementation of this community service involves the creation of attractive social media and the installation of innovative banner banners. The results were positive, as evidenced by the increase in sales turnover of Warung Gondrong which reached a significant level. This success is a reflection of the effectiveness of digital marketing strategies in supporting the growth and competitiveness of MSMEs in the modern era.